2017
DOI: 10.3389/fpls.2017.01812
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression, Protein–Protein Interaction and Evolutionary Analysis of the Seed Plant-Specific BIG GRAIN and BIG GRAIN LIKE Gene Family

Abstract: BIG GRAIN1 (BG1) is an auxin-regulated gene which functions in auxin pathway and positively regulates biomass, grain size and yield in rice. However, the evolutionary origin and divergence of these genes are still unknown. In this study, we found that BG genes are probably originated in seed plants. We also identified that seed plants evolved a class of BIG GRAIN LIKE (BGL) genes which share conserved middle and C-terminal motifs with BG. The BG genes were present in all monocot and eudicot species analyzed; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 104 publications
(132 reference statements)
1
18
0
Order By: Relevance
“…OsaBG1 encodes a membrane protein regulating auxin transport and sensitivity, and positively affecting plant biomass and seed size. The gene belongs to a small family containing nine members in spruce 86 . Auxin has long been known to act as a key hormone essential for the induction of vascular strands, cambial growth and secondary wall deposition [88][89][90][91] .…”
Section: Genetic Associations Detected and Modes Of Gene Action A Tomentioning
confidence: 99%
“…OsaBG1 encodes a membrane protein regulating auxin transport and sensitivity, and positively affecting plant biomass and seed size. The gene belongs to a small family containing nine members in spruce 86 . Auxin has long been known to act as a key hormone essential for the induction of vascular strands, cambial growth and secondary wall deposition [88][89][90][91] .…”
Section: Genetic Associations Detected and Modes Of Gene Action A Tomentioning
confidence: 99%
“…In addition, Liu et al () isolated a dominant mutant, big grain1‐D ( Bg1‐D ), that produces extra‐large grains caused by overexpression of the BG1 gene. BG1 encodes a novel membrane‐localized protein and may physically interact with auxin transporters (Liu et al ; Mishra et al ), and Bg1‐D mutants exhibit increased basipetal auxin transport and altered auxin distribution, suggesting a role in regulating auxin transport.…”
Section: Auxin and The Cereal Endospermmentioning
confidence: 99%
“…Public and proprietary maize genomes and transcriptomes were extensively searched for gene family members related to rice OS-BG1 (BIG GRAIN1) gene (Locus OS03g0175800). Mishra et al (2017) identified 10 candidate maize family members. We determined that there are 8 members of the maize BG1-related gene family with over 20% amino acid identity (AAID) to OS-BG1 (Table S1).…”
Section: Maize Bg1 Gene Familymentioning
confidence: 99%
“…Promoter analyses among native ZM-BG1H1 homologs OS-BG1 and BG1 homolog promoters were reported to possess auxin response-related motifs (Mishra et al, 2017). We initiated a de novo search for conserved motifs found in the proximal promoter, the first 1000 nts upstream from the ATG, for each of BG1 homologs across 5 species: ZM-BG1H1, the OS-BG1 and BG1 homologs from Sorghum, Brachypodium and Setaria ( Figure S7).…”
Section: Subcellular Localizationmentioning
confidence: 99%
See 1 more Smart Citation